2007
DOI: 10.1021/jp0689215
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of the Phosphorescent Trinuclear Copper(I) Complexes of Pyrazolates:  Insights from Theory

Abstract: Theoretical investigations have been performed to explore the optical properties of {[3,5-(CF3)(2)Pz]Cu}3 in monomeric and dimeric forms using TD-DFT approaches. The emission of all complexes originates from the lowest triplet excited-states (T1), and the corresponding emissive states are assigned as the mixture of the metal-centered charge transfer and ligand-to-metal charge transfer. The features of the emission spectrum are clarified in detail. The bulk emission spectrum of complex is mainly determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 105 publications
4
31
1
Order By: Relevance
“…Molecular geometry and optical properties of luminescent d 10 complexes have been found to show the characteristic of chemosensors in particular applications [22]. For example, trinuclear metal pyrazolate complexes with different from their substituents and metals on ligands have been reported to show interesting bright and tunable luminescence properties [23].…”
Section: Optical Properties Of Chemosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular geometry and optical properties of luminescent d 10 complexes have been found to show the characteristic of chemosensors in particular applications [22]. For example, trinuclear metal pyrazolate complexes with different from their substituents and metals on ligands have been reported to show interesting bright and tunable luminescence properties [23].…”
Section: Optical Properties Of Chemosensorsmentioning
confidence: 99%
“…6f, green dot). Such quenching of intensity in 100% indicates that the chairlike coordination geometry of Cu(I)-Cu(I) metallophilic interaction [4,[19][20][21][22][23][24][25][26][27]35] was totally disrupted through the columnar assembly of the weak intermolecular interaction. In this case, Cu(I) ions in one pyrazole ring are unable to form metal-metal interaction with other Cu(I) ions of the ligand.…”
Section: Sensing Capability Of Chemosensorsmentioning
confidence: 99%
“…19 Additional studies utilized the LAND2DZ basis set -RECP (relativistic effective core potential) combination, 20,21 or combined LANL2DZ for copper with the 6-31G* basis set for other atoms. [22][23][24][25] These studies, again, focused on geometrical aspects which were found to be sometimes exaggerated by the calculations. 22 Some of these studies sought to understand the relation between both the geometry and the electronic structure on the one hand, and different spectra of various copper complexes on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…22 Some of these studies sought to understand the relation between both the geometry and the electronic structure on the one hand, and different spectra of various copper complexes on the other hand. 23,24 Other studies tried to predict, based on the geometric preference of the complex, whether the ligands involved would actually bind copper 25 or attempted to determine the chemical softness/hardness of copper(I) based on trends in the heat of formation of copper with various ligands. 22 All these studies, however, due to the relatively low level of theory, dealt mainly with structure and electronic properties, rather than coordination number and absolute energies.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency calculations have been carried out to ensure that the optimized geometry has all positive frequencies and thus is a minimum on the potential energy surface. The first excited state (S 1 ) geometries have been optimized using the ab initio CIS approach [37] and previously this approach has been applied on mer-Alq3 and its derivatives [54][55][56][57][58][59][60][61][62][63], mer-AlND3 and its methyl derivatives [64] and other OLED materials [67][68][69][70][71] which has given reliable results. The absorption and emission spectra of these derivatives have been evaluated at by PBE0/6-31G(D) method using the B3LYP/6-31G(D) and CIS/6-31G(D) optimized geometries respectively.…”
Section: Computational Detailsmentioning
confidence: 99%